Survey of Ethnoveterinary Medicines Used to Treat Livestock Diseases in Omusati and Kunene Regions of Namibia - Eiki, Ndahambelela; Maake, Matome; Lebelo, Sogolo; Sakong, Bellonah; Sebola, Nthabiseng; Mabelebele, Monnye (Frontiers in Veterinary Science, 2022)
Many livestock farmers in rural areas cannot afford synthetic pharmaceutical drugs, they therefore, turn to indigenous knowledge as an alternative key to treating livestock diseases. However, ethnoveterinary practices in some rural parts of Namibia is not well documented despite its popularity. In this study, ethnoveterinary medicine used in the treatment of livestock diseases were surveyed to document this indigenous knowledge in Omusati and Kunene region of Namibia. Using semi-structured questionnaires to conduct interviews, data were collected from 100 local inhabitants in Omusati and Kunene regions of Namibia. The results showed that 15 plant species from 10 families were used to manage various livestock diseases. Plant leaves were commonly used, being crushed, soaked in water, and administered orally or topically. Skin infections were managed using the plant Aloe esculenta and Salvadora persica. Diarrhoea was treated using Ziziphus mucronata, Combretum collinum, and Colophospermum mopane. Ziziphus mucronata was also used in the treatment of mastitis. The plants Ximenia americana and Combretum imberbe were used to relieve eye infections in cattle, goats, and sheep. Retained placentas were treated with Acacia nilotica, Acacia erioloba, and Grewia flavescens. Fockea angustifolia roots were used to treat cattle suffering from anthrax. Therefore, current findings are the opportunities to scrutinize the plants for the discovery of new drug sources for livestock health management in the study area.